2017
DOI: 10.1016/j.jhazmat.2017.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-ethylene bridged PMO: A high capacity regenerable mercury adsorbent via intrapore mercury thiolate crystal formation

Abstract: Highly ordered thiol-ethylene bridged Periodic Mesoporous Organosilicas were synthesized directly from a homemade thiol-functionalized bis-silane precursor. These high surface area materials contain up to 4.3mmol/g sulfur functions in the walls and can adsorb up to 1183mg/g mercury ions. Raman spectroscopy reveals the existence of thiol and disulfide moieties. These groups have been evaluated by a combination of Raman spectroscopy, Ellman's reagent and elemental analysis. The adsorption of mercury ions was evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…It has been known that all thiols have an affinity for mercury ions as well as sulphides 25 , 41 . Therefore, it is not surprising that Me/Lig ratio is almost 1/1 for all studied samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known that all thiols have an affinity for mercury ions as well as sulphides 25 , 41 . Therefore, it is not surprising that Me/Lig ratio is almost 1/1 for all studied samples.…”
Section: Resultsmentioning
confidence: 99%
“…This urges a requirement for application of single-step methods in preparation of magnetite particles functionalized by 3-mercaptopropyl groups 24 . Moreover, it is known that thiol groups are easily oxidized to form disulfide bonds 25 , 26 that are no longer capable of ion-exchange interactions, which decrease their sorption capacity towards many metal ions 27 . Recently it has been demonstrated that introduction of an additional alkyl function into the ligand layer is capable to limit the unwanted interactions and stabilize single functional groups 28 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, an option that allows thiol groups to be obtained without involving the use of grafting or co-condensation processes is the use of the precursor 1-thiol-1,2-bis(triethoxysilyl)ethane, synthesized by Van Der Voort et al by thiol acid-ene chemistry [13]. This yielded a 100% thiol-functionalized PMO, which proved to have a high adsorption capacity and selectivity towards mercury ions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale application of the biological method is limited by parameters such as pH, temperature, and the content of oxygen for a microorganism. Among the numerous techniques, adsorption is the most widely utilized because of its advantages of cost-effectiveness, easy operation, and high efficiency at trace quantities, but its problems such as regeneration, poor selectivity, and secondary pollution still need further improvement.…”
Section: Introductionmentioning
confidence: 99%